Answer:
17476
Step-by-step explanation:
8(
)-(6+4)2
8(2187)-(10)2
17496-20
17476
Answer:
ummm i tried but.....
Step-by-step explanation:
Answer:
![$ \frac{\sqrt{3} - 1}{2\sqrt{2}} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B%5Csqrt%7B3%7D%20-%201%7D%7B2%5Csqrt%7B2%7D%7D%20%24)
![$ \frac{-(\sqrt{3} + 1)}{2\sqrt{2}} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B-%28%5Csqrt%7B3%7D%20%2B%201%29%7D%7B2%5Csqrt%7B2%7D%7D%20%24)
![$ - \frac{\sqrt{3} - 1}{\sqrt{3} + 1} $](https://tex.z-dn.net/?f=%24%20-%20%5Cfrac%7B%5Csqrt%7B3%7D%20-%201%7D%7B%5Csqrt%7B3%7D%20%2B%201%7D%20%24)
Step-by-step explanation:
Given ![$ \frac{11 \pi}{12} = \frac{3 \pi}{4} + \frac{\pi}{6} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B11%20%5Cpi%7D%7B12%7D%20%3D%20%5Cfrac%7B3%20%5Cpi%7D%7B4%7D%20%2B%20%5Cfrac%7B%5Cpi%7D%7B6%7D%20%24)
(A) ![$ sin(\frac{11\pi}{12}) = sin (\frac{3 \pi}{4} + \frac{\pi}{6}) $](https://tex.z-dn.net/?f=%24%20sin%28%5Cfrac%7B11%5Cpi%7D%7B12%7D%29%20%3D%20sin%20%28%5Cfrac%7B3%20%5Cpi%7D%7B4%7D%20%20%2B%20%5Cfrac%7B%5Cpi%7D%7B6%7D%29%20%24)
We know that Sin(A + B) = SinA cosB + cosAsinB
Substituting in the above formula we get:
![$ sin (\frac{3\pi}{4} + \frac{\pi}{6}) = \frac{1}{\sqrt{2}} . \frac{\sqrt{3}}{2} + \frac{-1}{\sqrt{2}}. \frac{1}{2} $](https://tex.z-dn.net/?f=%24%20sin%20%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%20%2B%20%5Cfrac%7B%5Cpi%7D%7B6%7D%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D%20.%20%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D%20%2B%20%5Cfrac%7B-1%7D%7B%5Csqrt%7B2%7D%7D.%20%5Cfrac%7B1%7D%7B2%7D%20%24)
![$ \implies \frac{1}{\sqrt{2}} (\frac{\sqrt{3} - 1}{2}) = \frac{\sqrt{3} - 1}{2\sqrt{2}}](https://tex.z-dn.net/?f=%24%20%5Cimplies%20%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D%20%28%5Cfrac%7B%5Csqrt%7B3%7D%20-%201%7D%7B2%7D%29%20%3D%20%5Cfrac%7B%5Csqrt%7B3%7D%20-%201%7D%7B2%5Csqrt%7B2%7D%7D)
(B) Cos(A + B) = CosAcosB - SinASinB
![$ cos(\frac{11\pi}{12}) = cos(\frac{3\pi}{4} + \frac{\pi}{6}}) $](https://tex.z-dn.net/?f=%24%20cos%28%5Cfrac%7B11%5Cpi%7D%7B12%7D%29%20%3D%20cos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%20%2B%20%5Cfrac%7B%5Cpi%7D%7B6%7D%7D%29%20%24)
![$ \implies \frac{-1}{\sqrt{2}}. \frac{\sqrt{3}}{2} - \frac{1}{\sqrt{2}} . \frac{1}{2} $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20%5Cfrac%7B-1%7D%7B%5Csqrt%7B2%7D%7D.%20%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D%20-%20%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D%20.%20%5Cfrac%7B1%7D%7B2%7D%20%24)
![$ \implies cos(\frac{11\pi}{12}) = cos(\frac{3\pi}{4} + \frac{\pi}{6}) $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20cos%28%5Cfrac%7B11%5Cpi%7D%7B12%7D%29%20%3D%20cos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%20%2B%20%5Cfrac%7B%5Cpi%7D%7B6%7D%29%20%24)
![$ = \frac{-(\sqrt{3} + 1)}{2\sqrt{2}}](https://tex.z-dn.net/?f=%24%20%3D%20%5Cfrac%7B-%28%5Csqrt%7B3%7D%20%2B%201%29%7D%7B2%5Csqrt%7B2%7D%7D)
(C) Tan(A + B) = ![$ \frac{Sin(A +B)}{Cos(A + B)} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7BSin%28A%20%2BB%29%7D%7BCos%28A%20%2B%20B%29%7D%20%24)
From the above obtained values this can be calculated and the value is
.
Answer:
y=4x would be one
Step-by-step explanation:
I hope its right...
Answer:
3 - 6p
Step-by-step explanation:
I think that's the answer :)
I hoped that helped!